Physical chemistry : (Prentice Hall, 2002)
This best-selling text presents the principles and applications of contemporary physical chemistry as they are used to solve problems in biology, biochemistry, and medicine. This text puts the study of physical chemistry for these students in context. Each chapter starts with sections on concepts and applications. These provide students with an overview of the physical chemistry principle under discussion and how that topic can be applied to solving biological and biochemical problems.